2018
DOI: 10.1016/j.ceramint.2018.06.170
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of > 99% phase-pure brookite TiO2 by hydrothermal conversion from Mg2TiO4

Abstract: The synthesis of pure brookite is generally much more difficult than that of pure anatase. The hydrothermal conversion, recently developed by Kozawa et al., is a facile method to synthesize brookite TiO 2 from inverse spinel-type Mg 2 TiO 4 under a mild hydrothermal condition e.g. in 1 M HCl solution at 100°C. However, slight rutile TiO 2 is usually co-existed under the reported conditions. The aim of this study is to prepare a high-purity brookite TiO 2 powder by the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Thus, based on the obtained data, it can be concluded that to control the formation process of titanium dioxide of any structural modification, we need to vary the conditions of TiO 2 • nH 2 O precipitation from the solution, alter the chemical composition of precursors [25,[27][28][29][30][31], or precipitation procedures [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, based on the obtained data, it can be concluded that to control the formation process of titanium dioxide of any structural modification, we need to vary the conditions of TiO 2 • nH 2 O precipitation from the solution, alter the chemical composition of precursors [25,[27][28][29][30][31], or precipitation procedures [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Another important area for nanocrystalline titanium dioxide is photocatalysis [13,[18][19][20][21][22][23]. Since the properties of TiO 2 nanoparticles strongly depend on phase composition, morphology and surface structure, many scientific papers focus on formation mechanism and design of various titanium oxide nanocrystals [1,[18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…There are many conventional methods for TiO 2 nanoparticles preparation, however, most of these methods involve several steps, long reaction time or high temperature to obtain nanocrystalline phases [7][8][9]. Due to these limitations, many current researches have focused on synthetic routes that follow the principles of green chemistry such as synthetic routes that consume less time, energy and reagents and that are viable for obtaining crystalline nanoparticles [10][11][12]. In particular, microwave-assisted synthesis has been extensively investigated due to its efficient and homogeneous energy transfer, rapid material processing with cost savings, moderate to high energy sources and related technology [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%